2017
DOI: 10.4038/slja.v26i1.8261
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound guided supraclavicular brachial plexus block using plain ropivacaine and ropivacaine with adjuvants

Abstract: Context: Ultrasound (US) guided supraclavicular brachial plexus block (SBPB) provides predictable dense blockade. Inclusion of additives to local anaesthetics alters the quality of blockade. Aim:To assess the block characteristics of ropivacaine alone and with additives in US guided SBPB. Materials and Methods:Prospective, double blinded randomized controlled trial. Sixty patients undergoing elective upper limb surgeries under SBPB were randomly allocated to one of 3 groups: Group RR (who received 30ml of 0.5%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 16 publications
0
17
0
Order By: Relevance
“…Only 6 studies reported the duration of analgesia and had complete data to pooling. [ 12 , 14 , 17 , 19 , 20 , 22 ] The result indicated that dexmedetomidine as an adjuvant prolonged the duration of analgesia significantly by an average of 303.04 minutes compared with the control group (MD, 303.04 minutes; 95% CI 228.84–377.24 minutes, I 2 = 86%; P < .00001) (Fig. 7 ).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Only 6 studies reported the duration of analgesia and had complete data to pooling. [ 12 , 14 , 17 , 19 , 20 , 22 ] The result indicated that dexmedetomidine as an adjuvant prolonged the duration of analgesia significantly by an average of 303.04 minutes compared with the control group (MD, 303.04 minutes; 95% CI 228.84–377.24 minutes, I 2 = 86%; P < .00001) (Fig. 7 ).…”
Section: Resultsmentioning
confidence: 96%
“…3 ). And adding dexmedetomidine to ropivacaine obviously decreased the time to sensory block onset both in groups with dosage greater [ 12 , 14 , 16 21 , 23 ] (MD, −2.97 minutes, 95% CI −4.94 to −1.01 minutes, I 2 = 86%; P = .003) and less [ 13 , 15 , 22 ] (MD, −6.96 minutes, 95% CI −11.85 to −2.06 minutes, I 2 = 86%; P = .005) than 50 μg (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…The full‐text manuscripts of the remaining 312 studies were assessed. After including studies from hand searches and revision of search, we identified a total of 100 studies for inclusion in this network meta‐analysis [32–131]. The study flow chart is in online Supporting Information Figure S1.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, pairwise meta‐analysis of 53 trials for sensory block duration [73–111, 113–122, 125, 126, 128, 129] and 53 trials for motor block duration [73–111, 113–122, 125, 126, 128, 129] comparing perineural dexmedetomidine vs. control arms did not reveal any sub‐group differences by indexing status (see online Supporting Information). Consequently, indexed and non‐indexed papers were pooled and analysed in the network, as decided a priori.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation